NILAI-NILAI KARAKTER TANGGUNG JAWAB PADA KEGIATAN KEPRAMUKAAN DALAM MENINGKATKAN HASIL BELAJAR SISWA DI MADRASAH ALIYAH NEGERI 2 MUARO JAMBI - Feri, Bastian; Huda, Syamsul; Hayat, Najmul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the common problem of students’ lack of responsibility, which contributes to low learning outcomes, particularly in the subject of Aqidah Akhlak at State Islamic Senior High School 2 Muaro Jambi. The purpose of this research was to analyze the values of responsibility character developed through scouting activities and their role in improving students’ learning outcomes. This study employed a descriptive qualitative approach. The research subjects consisted of Aqidah Akhlak teachers as key informants, scout instructors and the principal as supporting informants, and students of class XI 1 and XI 2 as respondents selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students’ learning outcomes varied; although most students achieved the Minimum Completeness Criteria (75), some remained below the standard. Students who demonstrated responsible behaviors—such as completing assignments on time, participating actively in class, and avoiding academic dishonesty—tended to achieve higher scores. Scouting activities fostered responsibility through self-discipline, accountability to others, and active participation. Supporting factors included students’ interest, instructors’ competence, institutional support, facilities, and parental involvement, while inhibiting factors involved lack of discipline, absenteeism, and peer influence. Efforts to strengthen responsibility values were conducted through advice, role modeling, task assignment, punishment, and reward systems. These findings indicate that the cultivation of responsibility character through scouting activities contributes positively to improving students’ learning outcomes.